2018
DOI: 10.1017/s0272263118000244
|View full text |Cite
|
Sign up to set email alerts
|

Social Attitudes and Speech Ratings

Abstract: This study examined whether social bias manipulation can influence how naïve multiage listeners evaluate second language (L2) speech. Sixty native English-speaking listeners (Montreal residents) rated audio recordings of 40 Quebec French speakers of L2 English for five dimensions of oral performance (accentedness, comprehensibility, segmental accuracy, intonation, flow) using 1,000-point continuous scales. Immediately before rating, 20 listeners heard critical comments about Quebec French speakers’ English lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 53 publications
1
24
1
Order By: Relevance
“…With respect to our first research question, we failed to replicate Reid et al (2019). We found no effect of social bias in our study and no effect of age.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…With respect to our first research question, we failed to replicate Reid et al (2019). We found no effect of social bias in our study and no effect of age.…”
Section: Discussioncontrasting
confidence: 77%
“…
This study conceptually replicated and extended Reid, Trofimovich, and O'Brien (2019), who found that native English speakers could be biased positively (or negatively) relative to a control condition in terms of how they rate non-native English speech. Our internetbased study failed to replicate Reid et al across a wider population sample of "native" speakers (n = 189).
…”
supporting
confidence: 80%
See 2 more Smart Citations
“…In light of our results suggesting that self‐assessment (reliance on self‐confidence) can successfully guide L2 learning, training individuals to become more accurate at assessing their own perception and production can lead to better learning outcomes and facilitate L2 learning. This is important as listeners’ assessment of L2 speakers’ production can be unstable and vary as a function of the listeners’ age and native language (Saito et al., 2019) and can be prone to social bias (Reid et al., 2019) and task effects (Crowther et al., 2018). The hypothesis that training metacognition can increase the efficiency of L2 learning is further supported by research on the use of metacognition in classroom teaching, in a broader sense, showing that metacognitive instruction can enhance the effectiveness of corrective feedback (Sato & Loewen, 2018).…”
Section: Discussionmentioning
confidence: 99%